The Role of Digital Leadership and Digital Transformation under the influence of Covid 19 - Rahko, Kun (My University, 2022)
Leadership plays an essential role in the management of an organization since it would sometimes determines the survival of the organization. Leadership reflects how the leaders of organizations would deploy the resources and manpower of the organizations, and what resolutions the leaders would take in urgent situations. However, organizations encountered a huge hurdle under COVID-19 since it has cast impediments to the operations of the companies. This paper aims to explore the role of digital leadership in digital transformation during the pandemic. In addition, this paper also explores the way that leaders could push forward the digital transformation to enable the company to adapt new market environment that their companies are in. Therefore, this paper capitalized on the research opinion of Saunders with interpretivism as the research philosophy, and the quantitative method was adopted to enable the execution of an interview. The paper found that digital leadership and digital transformation can advance the development of organizations, which is mainly demonstrated by the improvement of confidence in digital leadership. Besides, the productivity, self-efficiency, and self-sufficiency of employees would be enhanced, thereby providing more opportunities for employees. This paper also found that digital transformation could drive the digital leadership of organizations. Furthermore, leaders' rethinking was also enhanced so that leaders could figure out what approaches should be taken in an emergency. All of these findings show that digital transformation has a proactive impact on digital leadership.
Keywords: leadership (activity); leadership (properties); digitalisation; pandemics; COVID-19; enterprises; innovations; change; managers and executives; organisations (systems); fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business